Mesoscale Convective Systems in the Asian Monsoon Region From Advanced Himawari Imager: Algorithms and Preliminary Results. Issue 4 (23rd February 2019) - Chen, Dandan; Guo, Jianping; Yao, Dan; Lin, Yanluan; Zhao, Chuanfeng; Min, Min; Xu, Hui; Liu, Lin; Huang, Xiaomeng; Chen, Tianmeng; Zhai, Panmao
Abstract: The knowledge of mesoscale convective system (MCS) in the Asian monsoon region remains still deficient due to the limited available data and less powerful algorithms. Here, using the data from Advanced Himawari Imager onboard Himawari‐8 (HW8), an improved algorithm combining the area overlapping with the Kalman filter is developed, which captures much smaller MCSs that are unavailable otherwise. Several influential factors like the overlapping rate and splitting/merging in the area overlapping method, and the initial state variable in the Kalman filter method, all of which were less appreciated, are handled explicitly. The occurrence frequency, and moving trajectory of two types of MCS, including the ordinary MCS and superconvective system, has been comprehensively examined in the Asian monsoon region for the warm season (April to September) of 2016. Comparison analyses with ground precipitation and radar measurements confirm the good performance of our algorithm. In particular, the moving direction of MCS strongly depends on latitudes, so does the horizontal velocity. Compared with over ocean, the frequency of MCSs dominates over land or along coasts in the tropics, where strong moisture flux convergence is frequently observed in the low troposphere. In addition, the MCSs detected in eastern China can roughly capture the meridional propagation over time, which corresponds well to the precipitation belts linked to Meiyu front systems. The superconvective systems dominate over the Bay of Bengal and South China Sea due to the large‐scale circulation. Our findings provide new insights to spatiotemporal patterns of MCSs during warm season in the Asian monsoon region. Key Points: A novel algorithm is proposed to track mesoscale convective systems, combining the area overlapping method with the Kalman Filter method This algorithm provides us more opportunities to capture very small MCSs that might not otherwise be captured Major features of mesoscale convective systems, including trajectory, horizontal movement and frequency in whole East Asia are explored